L’absence et la compensation : en l’absence de, faute de, à défaut de, par manque de - Thierry Ruchot (Studii de Lingvistica)
In this article, I study a group of complex prepositions linked semantically by the notion of absence of an entity or event, seen as a circumstance for another situation: en l’absence de, faute de, à défaut de, par manque de. I first discuss the semantics of the constituent nouns of these prepositions as a prerequisite to studying their role in the constitution of the prepositions focussed on. I then argue for abandoning the very common treatment of prepositions as relators, showing that the prepositions I consider cannot be treated as mere relators. I then examine tests that show that the members of this group belong to complex prepositions, while demonstrating the proximity of some of them to other constructions, such as participial clauses. Next, I study the regime of these prepositions, showing that they present important differences that I try to explain by their structure. Finally, I analyze the syntactic and semantic differences between the various prepositions.